PENGARUH CITRA MEREK (BRAND IMAGE) TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK SAMSUNG PADA PT. SAMSUNG ELECTRONICS INDONESIA PEKANBARU - FAKHRI, RIZQI (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
Technology and science that are developing rapidly give rise to modern technological products for customers. The technology that exists today is a technology that serves humans and is not just a sophisticated technology created for sophistication itself. One of them is the field of communication and information technology. The change in the advancement of communication and information technology makes the increase in the use of mobile phones faster. Along with the development of technology, the function of cellphones is not only as a telephone and SMS tool but has been referred to as a smartphone information search and entertainment tool. With a good brand image of a company's product, it is able to make the company maintain its continuity so that it continues to grow and survive amidst the onslaught of competitors and the same product. To get a good brand image label from customers, a company is able to make innovations and evaluate the products being marketed. Companies must also maintain quality, consistency, perform maintenance, and maintain good relations with consumers. The number of samples in this study were 87 people. From the results of the item validity test, the overall statement between the competence and performance variables was declared valid because the value rcount > rtable (0.2108). The results of simple linear regression obtained the value of Y = 25.527 + 0.381. From the results of the partial test or t test, the tcount value (5,641)> from the ttable value (1,98827) with a significant level of 0.000 <0.05 means that the brand image variable has a significant effect on the Purchase Decision variable. And the value of the coefficient of determination R2 is 0.272, meaning that the influence or the magnitude of the influence of brand image on purchasing decisions is 0.272 or 27.2%, while the remaining 72.8% is influenced by other variables not examined in this study.